ARBITRASE ISLAM DALAM PERSPEKTIF ISLAM DAN HUKUM POSITIF - Setiady, Tri (Lampung University, 2015)
The business world today has grown indefinitely so as to break through the dimensions of human life and behavior of the economy into banking minded and change the values and aspects of the business itself, either legally or sociologically. Business development with the pattern and any system can not be separated from the financial institution whose name the bank. Banking deregulation undertaken by the government has been precise to support the economy in order to develop better. With the enactment of Law Number 10 of 1998 concerning amendments to the Law Number 7 of 1992 on Banking, is an opportunity and provide an opportunity for Muslims to establish a bank based on Islamic Sharia, as support to the business world and the economy of the people. With the presence of banks based on Islamic Sharia is expected to accelerate the economic revival in the race entering the era of globalization.Keywords: Arbitration Islam, the Islamic Perspective, Positive LawÂ